Fluid-to-fluid scaling for convective heat transfer in tubes at supercritical and high subcritical pressures - Zahlan, H.; Groeneveld, D.C.; Tavoularis, S. (International journal of heat and mass transfer, 2014)
Following a review of two recent sets of fluid-to-fluid scaling laws for supercritical heat transfer and a discussion of their possible limitations, we have proposed two additional sets of scaling laws, which take into account empirically adjustable versions of the Dittus–Boelter correlation and which are applicable to both the supercritical and the high subcritical flow regions. We have compiled a database of heat transfer measurements in carbon dioxide flowing upwards in vertical heated tubes that are free of deterioration or enhancement. We then applied the four sets of scaling laws to these data to compute values of the water-equivalent heat transfer coefficient and compared these values to predictions of a transcritical look-up table, which was earlier shown to represent well a large compilation of measurements in water at supercritical and high subcritical pressures. It was shown that the two earlier methods systematically overestimated the heat transfer coefficient in water and also introduced significant imprecision. In contrast, the two proposed methods of scaling introduce no bias and have lower precision uncertainties than those of the previous scaling methods.